Separation of Labeled Gold Nanoparticles (GNPs) by Capillary Electrophoresis Review of the Literature - Alshehri, Hessa (British Journal of Healthcare and Medical Research, 2023)
Nanoparticles (NPs) are particles ranging in size up to hundreds of nanometers and possess unique characteristics such as a large surface area to volume ratio and special chemical properties. With applications in advanced chemistry, physics, medicine, and material science, their distinctiveness has particularly impacted the field of separation sciences. Recent developments have explored NPs in various applications like microchip technologies and surface coatings, and various types such as zeolite, carbon nanotubes, and latex have been utilized for separation purposes (Sardar et al., 2019; Sýkora et al., 2017; Sperling et al., 2018; Brust et al., 2015). This review highlights the essential role of NPs in separation sciences, showcasing their versatility and relevance across diverse fields.